The Influence of People's Business Credit (KUR) on UMKM Income Levels in Tinggimoncong District Gowa District - Nurfadhila Utami (Income Journal Of Economics Development, 2023)
This study aims to determine the effect of People's Business Credit Assistance (KUR) on the Income Level of Micro, Small and Medium Enterprises in Tinggimoncong District, Gowa Regency. The number of respondents as many as 25 respondents, the analytical method used is simple linear regression analysis, the type of research used is quantitative research methods. The results showed that the People's Business Credit Assistance (KUR) in Tinggimoncong District, Gowa Regency had a positive and significant effect on the Income Level of Micro, Small and Medium Enterprises in Tinggimoncong District, Gowa Regency. This is evidenced by the results of the calculation of the t-test (partial) the value of t_count is 4.457 and t_table is 1.713 with a significant level of 0.000. Because the value of t_count is greater than t_table with a significance less than 0.05 (5%), this study succeeded in proving the hypothesis which states that "The Provision of People's Business Credit (KUR) has a positive and significant impact on the income level of Micro, Small and Medium Enterprises in Tinggimoncong District, Gowa Regency” this is caused by variable indicators in the form of independent variables and dependent variables